Flaws - Pepin-Neff, Christopher L. author. aut Link
XVII, 192 p. 21 illus., 1 illus. in color.
Keywords: This book examines the policymaking process following highly emotional events. It focuses on the politics of shark “attacks” by looking at policy responses to tragic shark bites in Florida, Australia, and South Africa. The book reviews these cases by identifying the flaws in the human-shark relationship, including the way sharks are portrayed as the enemy, the way shark bites are seen as intentional, and how policy responses appear to be based on public safety. Flaws identifies politicians as the true sharks of this story for their manipulation of tragic circumstances to protect their own interests. It argues that shark bites are ungovernable accidents of nature, and that we are “in the way, not on the menu.” Christopher Pepin-Neff is Senior Lecturer in Public Policy at the University of Sydney, Australia. His research looks at theories of the policy process by focusing on highly emotional issues such as LGBTQI politics and the "politics of shark attacks." .